A century of homeopaths : their influence on medicine and health - Davidson, Jonathan (Springer New York, 2014)
As the values of integrative medicine continues to grow, alternative points of view and treatments are increasing in acceptance and prevalence.  Homeopathic medicine is considered an important root to this approach.  However, contributions of homeopathically qualified doctors have long been overlooked.   A Century of Homeopaths is a detailed account of the many homeopaths who have contributed to medical progress since 1840.  The accomplishments of over 100 homeopaths form the organizing structure of the book - many of whom have been lost to history.  The text describes the ways in which homeopaths have influenced medical practice, research and public health, as well as the seminal effect of homeopaths in the emergence of today's medical specialties and in social reform, thus providing insights to healthcare professionals, researchers, students and medical historians.